Retroperitoneal Pleomorphic Liposarcoma Mimicking Adrenal Cancer in F-18 FDG PET/CT - Yoon, Minki (Springer-Verlag, 2010)
Liposarcoma is the second most common type of soft tissue sarcoma, but pleomorphic liposarcoma is the least common subtype. We present the case of a 42-year-old man who had experienced intermittent left flank pain for a month. A large soft-tissue mass was detected by ultrasonography in a local clinic, and he was referred for further evaluation. Positron emission tomography/computed tomography (PET/CT) with F-18 fluoro-2-deoxy-D-glucose (F-18 FDG) showed intense uptake in the retroperitoneal mass, which mimicked an adrenal cancer. The patient underwent left radical nephroadrenalectomy, and the tumor was revealed to be a pleomorphic liposarcoma upon pathological examination. When there is a large retroperitoneal mass with intense F-18 FDG activity, the possibility of a pleomorphic liposarcoma should be considered.